2022
DOI: 10.1111/jonm.13856
|View full text |Cite
|
Sign up to set email alerts
|

Organizational culture and readiness for evidence‐based practice in the Kingdom of Saudi Arabia: A pre‐experimental study

Abstract: Aim This study aims to establish postgraduate students’ perceptions of the organizational culture and readiness for evidence‐based practice of their workplaces in the Kingdom of Saudi Arabia. Background Nurse shortages and a reliance on a transient nurse workforce have long been a challenge in the Kingdom of Saudi Arabia. Developing a home‐grown nurse workforce, a key objective of the Government of Saudi Arabia, can help to address this. Evidence‐based practice offers a mechanism to address this. Evidence‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The survey showed low scores on knowledge about EBP and Theme 5 stated lack of knowledge and difficulties with the EBP process. Many hospitals studied identified the need for a formal EBP education (Galiano et al., 2020), a unit‐based EBP culture, stronger EBP organizational structures, EBP mentorship (Melnyk et al., 2021), and other EBP resources (Cleary‐Holdforth et al., 2022) that are associated with better nurse and patient outcomes (Melnyk & Fineout‐Overholt, 2023). The other factor that facilitates practice changes is nurse‐led EBP projects (Schutte et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survey showed low scores on knowledge about EBP and Theme 5 stated lack of knowledge and difficulties with the EBP process. Many hospitals studied identified the need for a formal EBP education (Galiano et al., 2020), a unit‐based EBP culture, stronger EBP organizational structures, EBP mentorship (Melnyk et al., 2021), and other EBP resources (Cleary‐Holdforth et al., 2022) that are associated with better nurse and patient outcomes (Melnyk & Fineout‐Overholt, 2023). The other factor that facilitates practice changes is nurse‐led EBP projects (Schutte et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Holdforth et al, 2022) that are associated with better nurse and patient outcomes(Melnyk & Fineout-Overholt, 2023). The other factor that facilitates practice changes is nurse-led EBP projects(Schutte et al, 2022).…”
mentioning
confidence: 99%
“…Furthermore, the leaders did not arrange updates and research methods training. A pilot experimental study reported that a conducive environment and the availability of necessary resources to support evidence-based practice are needed [ 18 ]. Hence, hospital managers are suggested to establish and sustain internet access and other resources to boost EBP.…”
Section: Discussionmentioning
confidence: 99%
“…Suppose a particular measure is a priority for an organisation. In that case, if it is established by the board of directors or the nursing department, and if this option is also clearly communicated, the employees must align themselves with it, integrating the directive and acting accordingly [75,76].…”
Section: Discussionmentioning
confidence: 99%